Coating based on cassava starch and chitosan in maintenance of vacuum packaged shrimp quality (Research, Society and Development, 2020)
Shrimp is a product with good nutritional characteristics and strong market appeal, however, highly susceptible to microbiological contamination. For this reason, the use of appropriate preservation methods is essential to guarantee the quality of this food throughout its marketing chain. Conventional methods of shrimp preservation make use of non-biodegradable plastic packaging associated with refrigeration and vacuum. As an alternative to these plastic packages, coatings based on biopolymers such as polysaccharides and proteins can be used. In this work, the quality of the shrimp covered with films from cassava starch and chitosan was evaluated. Fresh shrimp were collected, peeled, and dipped in filmogenic solutions of cassava starch, chitosan, and mixed cassava starch with chitosan (1:1), a negative control was performed. The samples were stored in vacuum packages for six days, and on days 3 and 6, three repetitions of mesophilic bacteria count, pH, and humidity analysis were performed. The groups with coatings presented lower bacterial counts than the control group, especially the groups containing chitosan.  The pH and humidity changed during the days of experiment only in the group covered with cassava starch and control group, being pH variation associated with the increase of mesophilic bacteria count in these groups. The influence of the application of the coating on the conservation of the shrimp, in addition to creating a barrier around it, shows antimicrobial properties when considering chitosan, and may be a promising method for the conservation of minimally processed food.